(untitled) (World Bulletin of Management and Law, 2026)
This article discusses the legal foundations of suretyship in Islamic law as a means of ensuring the performance of obligations in civil law. It examines the permissibility of suretyship, its conditions, the legal status of a legally responsible person, and the types of suretyship such as personal surety and financial surety, as well as their specific characteristics. The article also describes the forms in which suretyship is applied in modern banking